Bowen Ratio Measurements of Energy Budget Components over Various Ecosystems in Mymensingh, Bangladesh - Khatun, R; Farukh, MA; Miyata, A; Baten, MA (Journal of Environmental Science and Natural Resources, 2015)
Surface energy budget components were measured over four different surfaces in the campus of Bangladesh Agricultural University, Mymensingh, Bangladesh (24.75ºN, 90.5ºE) at the beginning of dry season (August to December 2004) using Bowen Ratio Energy Balance (BREB) technique. Under sufficient soil moisture conditions, surface energy budget during the study period was characterized by dominant latent heat flux (79% to 92% of net radiation) and negligibly small sensible heat flux with small modification by vegetation. DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22139 J. Environ. Sci. & Natural Resources, 7(1): 21-25 2014